2015
DOI: 10.3892/etm.2015.2254
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine reverses doxorubicin resistance through the PI3K/Akt signaling pathway in K562/A02 human leukemia cells

Abstract: Drug resistance is an important obstacle to human leukemia therapeutics. Piperlongumine has previously demonstrated the ability to suppress certain human tumor processes; however, the ability of piperlongumine to reverse the drug resistance of human leukemia and its mechanism of action have not yet been clearly elucidated. In this study, the doxorubicin resistance reversal effect of piperlongumine on K562/A02 human leukemia cells and the underlying mechanism were investigated. The results indicated that piperl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Piplartine also inhibited the viability of bone marrow mononuclear cells from the patients with myeloid leukemias, but not from patients with myelodysplastic syndrome, which induced apoptotic and autophagic cell death via activation of ROS-p38/JNK pathways [22] . Piplartine also reversed doxorubicin resistance in K562/A02 human leukemia cells by PI3K/Akt pathway [21] . Moreover, piplartine also induced apoptosis through activation of ERK signaling in cholangiocarcinoma and colon carcinoma cell lines [51] , [52] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Piplartine also inhibited the viability of bone marrow mononuclear cells from the patients with myeloid leukemias, but not from patients with myelodysplastic syndrome, which induced apoptotic and autophagic cell death via activation of ROS-p38/JNK pathways [22] . Piplartine also reversed doxorubicin resistance in K562/A02 human leukemia cells by PI3K/Akt pathway [21] . Moreover, piplartine also induced apoptosis through activation of ERK signaling in cholangiocarcinoma and colon carcinoma cell lines [51] , [52] .…”
Section: Discussionmentioning
confidence: 92%
“…Although its cytotoxic properties have been known for over three decades, the great interest in this molecule has arisen after its cytotoxicity and ability to induce the production of reactive oxygen species (ROS) selectively in cancer cells were described [11] , [12] . Currently, the cytotoxic potential of piplartine and/or its derivatives have been extensively examined in different types of cancer, including leukemia [12] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the established PC3/R cell line demonstrated significant drug resistance to doxorubicin. Due to data published from previous studies, which provided evidence that the PI3K/AKT pathway regulates the chemotherapeutic resistance of cells ( 15 , 16 ), the activation of PI3K and AKT in PC3/R cells compared with parental PC3 cells, in response to doxorubicin, was investigated. Notably, activation of the PI3K/AKT pathway was significantly increased in PC3/R cells compared with parental PC3 cells, in the presence or absence of equal doses of doxorubicin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PL exhibits a synergistic effect with various chemotherapeutic drugs, including cisplatin and paclitaxel, in ovarian, head and neck cancer (24,26,52). PL suppressed the expression of P-glycoprotein, ATP binding cassette subfamily B member 1, ATP binding cassette subfamily C member 1, survivin, and phospho-Akt, as well as the transcriptional activities of NF-κB and TWIST, which reversed doxorubicin resistance in a breast cancer cell line (53).…”
Section: Discussionmentioning
confidence: 97%